2007
DOI: 10.1182/blood-2006-08-041384
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts support B-lymphocyte commitment and differentiation from hematopoietic stem cells

Abstract: Early B lymphopoiesis in mammals is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
330
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(346 citation statements)
references
References 24 publications
14
330
0
2
Order By: Relevance
“…Furthermore, reduced marrow IL-6 mRNA expression in Prg4 mutant mice may contribute to decreased frequency of B-lymphocytic cells, because IL-6 supports physiological B-lymphopoiesis. 28,53,54 Similar to Prg4 mutant mice, mice with an osteoprogenitor cell G s ␣ deficiency (a downstream mediator of the PPR) have decreased peripheral blood and marrow B-lymphocytic cells, 55 suggesting that osteoblast cell signaling also could play a role in Prg4 mutant mice. The unexpected finding that PTH induced normalization of peripheral blood neutrophils and marrow B-lymphocytic cells in Prg4 mutant mice to wild-type levels may be associated with the PTH-induced increase in marrow SDF-1 protein in Prg4 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reduced marrow IL-6 mRNA expression in Prg4 mutant mice may contribute to decreased frequency of B-lymphocytic cells, because IL-6 supports physiological B-lymphopoiesis. 28,53,54 Similar to Prg4 mutant mice, mice with an osteoprogenitor cell G s ␣ deficiency (a downstream mediator of the PPR) have decreased peripheral blood and marrow B-lymphocytic cells, 55 suggesting that osteoblast cell signaling also could play a role in Prg4 mutant mice. The unexpected finding that PTH induced normalization of peripheral blood neutrophils and marrow B-lymphocytic cells in Prg4 mutant mice to wild-type levels may be associated with the PTH-induced increase in marrow SDF-1 protein in Prg4 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…BM osteoblasts were also shown to promote B-cell differentiation of murine hematopoietic progenitors in culture and depletion of BM osteoblasts in Col2.3D-TK mice resulted in a loss of pre-B-cell content in vivo. 22 The function of BM osteoblasts in regulating HSC fate was first suggested by Taichman et al, 23 who showed that in vitro culture of human BM CD34 þ cells with human osteoblasts supported a 3-4-fold expansion of long-term culture-initiating cells in vitro. More recently, the function of the BM osteoblast in regulating HSC pool size was demonstrated by Calvi et al, 4 who showed that activation of the parathyroid hormone/parathyroid hormone receptor in vivo increased BM osteoblast and trabecular bone content, yielding a significant increase in BM HSC numbers.…”
Section: Concept Of the Hematopoietic Stem Cell (Hsc) Nichementioning
confidence: 99%
“…9,14 Role of the BM osteoblast With advances in mouse genetics and microscopy, the function of the BM osteoblast in regulating hematopoiesis and HSC homeostasis has been demonstrated. 4,5,14,[21][22][23][24] Human osteoblasts were shown by Taichman and Emerson 21 to regulate the myeloid differentiation of human CD34 þ progenitor cells in culture via the production of granulocyte colony stimulating factor. BM osteoblasts were also shown to promote B-cell differentiation of murine hematopoietic progenitors in culture and depletion of BM osteoblasts in Col2.3D-TK mice resulted in a loss of pre-B-cell content in vivo.…”
mentioning
confidence: 99%
“…Osteoblasts also support B-cell commitment and differentiation [22][23][24]. However, the function of Wnt signaling in osteoblastsupported B-cell development remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, noncanonical Wnt signaling is also reported to sustain HSCs maintenance and aging [20,21]. Osteoblasts also support B-cell commitment and differentiation [22][23][24]. However, the function of Wnt signaling in osteoblastsupported B-cell development remains controversial.…”
mentioning
confidence: 99%